Periodic Catatonia: Long-term Treatment With Lamotrigine. Issue 4 (July 2021) - Konstantinou, Gerasimos; Papageorgiou, Charalabos C.; Angelopoulos, Elias
Abstract : Periodic catatonia is a rare form of catatonia, characterized by episodes occurring in a cyclic pattern with clinical features of combined stupor and excitement, with intervals of remission. Although periodic catatonia is not common, it is an urgent condition, requiring hospitalization for evaluation and treatment. The management of periodic catatonia is quite challenging, mainly because of the unknown pathophysiological mechanisms involved in the onset of this clinical entity, which are less clear than in other forms of catatonia. Although positive trials of several medications in the acute phase of periodic catatonia have been published, available literature concerning the prevention of recurrent catatonic episodes is scarce. Here, we present the case of a patient with periodic catatonia in which long-term treatment with lamotrigine appears to have acted prophylactically in reducing the occurrence and severity of new catatonic episodes. A better understanding of the mechanisms involved in the pathophysiology of periodic catatonia and increasing psychiatrists' and physicians' awareness of the presentation of this clinical entity could be of benefit in shedding light on the most appropriate treatment approach. However, further clinical studies are needed before any firm recommendations can be made.